Increases in VO2max with "live high-train low" altitude training: role of ventilatory acclimatization - Wilhite, D. P.; Mickleborough, T. D. (European Journal of Applied Physiology, 2013)
The purpose of this study was to estimate the percentage of the increase in whole body maximal oxygen consumption ( VO2max) that is accounted for by increased respiratory muscle oxygen uptake after altitude training. Six elite male distance runners ( VO2max = 70.6 ± 4.5 ml/kg/min) and one elite female distance runner ( VO2max = 64.7 ml/kg/min) completed a 28-day "live high-train low" training intervention (living elevation, 2,150 m). Before and after altitude training, subjects ran at three submaximal speeds, and during a separate session, performed a graded exercise test to exhaustion. A regression equation derived from published data was used to estimate respiratory muscle VO2 ( VO2RM) using our ventilation ( VE) values. VO2RM was also estimated retrospectively from a larger group of distance runners (n = 22). VO2max significantly (p < 0.05) increased from pre- to post-altitude (196 ± 59 ml/min), while VE at VO2max also significantly (p < 0.05) increased (13.3 ± 5.3 l/min). The estimated VO2RM contributed 37 % of dVO2max. The retrospective group also saw a significant increase in VO2max from pre- to post-altitude (201 ± 36 ml/min), along with a 10.8 ± 2.1 l/min increase in VE, thus requiring an estimated 27 % of d VO2max. Our data suggest that a substantial portion of the improvement in VO2max with chronic altitude training goes to fuel the respiratory muscles as opposed to the musculature which directly contributes to locomotion. Consequently, the time-course of decay in ventilatory acclimatization following return to sea-level may have an impact on competitive performance.